Retention of antibacterial activity and bacterial colonization of antiseptic-bonded central venous catheters - Bach, Alfons; Schmidt, Heinfried; Böttiger, Bernd W.; Schreiber, Burkhard; Böhrer, Hubert; Motsch, Johann; Martin, Eike; Sonntag, Hans-Günther (The journal of antimicrobial chemotherapy, 1996)
We determined how long antiseptic impregnation with silver sulphadiazine and chlorhexidine (SCC) on polyurethane central venous double- or triple-lumen catheters is retained in vivo. A total of 116 antiseptic catheters were tested for antibacterial activity in an in-vitro bioassay after various periods of iv catheterization. Segments from the subcutaneous (sc) and intravenous (iv) portions of the catheters were cultured. The results of test antiseptic catheters were compared with those from 117 noncoated control (c) catheters. Retention of antibacterial activity followed an exponential curve and lasted for up to 520 h after catheter insertion. Significant differences (P=0.0001) between SSC and C catheters were noticed with regard to the quantitative level of bacterial colonization (SSC-sc 87 ± 34 vs C-sc 584±122; SSC-iv 52±17 m C-iv 286±57; all values are given as mean cfu±S.E.M.), and the frequency of bacterial colonization (SSC-sc 20.7% vs C-sc 38.5%, P=0.0047; SSC-iv 18.1% vs C-iv 30.8%, P=0.0361). There was no significant difference between the incidence of catheter-related bacteraemia in the test (n=0) and control groups (n=3) (P=0.2573). Further prospective studies are required to delineate the role of antiseptic catheters in preventing catheter-related infections.